The Design of Fishing Village Tourism Banjar Belawan - Dwira Nirfalini Aulia; Muthia Faradiba (International Journal of Architecture and Urbanism, 2017)
The design of Kampung Wisata is intended to improve the living standards and environmental quality of the Kampung Nelayan area. As we know that, the location is the formation of slum areas whose land ownership is still illegal and the majority of the population work as low-income fishermen. These conditions cause the environment look too grubby with scattered rubbish and the lack of environmental utilities. Though in addition, Kampung Nelayan region, particularly Kampung Banjar has a variety of potential that can be used as a capital to developed into the tourist attraction. This also can be used as a place to develop slum areas become a better place which can compete in the future.